What do Asian men consider as important masculinity attributes? findings from the asian men's attitudes to life events and sexuality (MALES) study - Ng, C.J.; Tan, H.M.; Low, W.Y. (2008)
Background: Masculinity plays an important role in shaping men's help-seeking behaviour. However, what men consider as important attributes of masculinity and how these attributes are related and vary with age in different Asian countries remains unknown. This study aimed to find out about Asian men's perception of masculinity. Methods: Five Asian countries (China, Japan, Korea, Malaysia and Taiwan) participated in this cross-sectional study in 2005/6. A total of 10,934 men aged 21-75 years were interviewed via computer-assisted telephone interviews and street interceptions. A standardised questionnaire based on the Men's Attitudes to Life Events and Sexuality (MALES) study was modified and used to capture men's views on masculinity attributes. Results: Men's views about the most important masculinity attributes varied from country to country. Overall, the majority considered 'having a good job' (20.3), 'being seen as a man of honour' (15.6) and 'being in control of his own life' (14.6) as the most important attributes and this observation did not vary with age. However, the relative importance of these attributes differed across the five countries which participated in this study. Conclusions: There were variations in men's views on masculinity across the five Asian countries but their perceptions appear to remain consistent with age. This study calls for more research into the role of masculinity in the understanding and promotion of men's health. (C) 2008 WPMH GmbH. Published by Elsevier Ireland Ltd.